Evaluación de la calidad del agua y aforo del Río Pichán en el tramo 17 m 770421 9990203 (UTM)- 17 m 770302 9994845 (UTM), Parroquia San Miguel de Nono - Rivadeneira Toro, Daniel Mauricio (2015)
The current study was aimed to evaluate the water quality of the Pichán river, which it is located at the parish of San Miguel de Nono. This evaluation was based on the identification and assessment of the water between two points of the river that crosses the urban rural parish, for which the monitoring was carried out in six different checkpoints and sampling along the river, for a period of three months between December of 2014 and February of 2015. The samplings were made in accordance with national and international methodologies and the analysis were performed at the Laboratorio Central de Control de la Calidad Del Agua from the EPMAPS through validated and approved techniques. The final results were interpreted with the national regulations, identifying important changes in the BOD, COD and Total Coliform, which were influenced by the direct discharge of domestic and industrial wastewater along rural parish San Miguel de Nono. Finally, through the development of different kinds of matrix indicative contamination factors the net impact of the activities in the parish San Miguel de Nono was determined on Pichán River, concluding that the water quality is at normal levels and it is responsibility of the Nono is Government to keep it that way.